The crowds in the Gospel of Matthew - Cousland, J. R. C. (Novum Testamentum, Supplements, 2002)
This volume identifies the crowds ( ochloi ) in the Gospel of Matthew and explains their character and function. It argues that a proper appreciation of the crowds is essential to an understanding of salvation history in the gospel. The book identifies the crowds as Jewish, and establishes that both the positive and negative characterizations of the crowds correspond to portrayals of Israel drawn from the Hebrew Scriptures. It concludes that the crowds are also meant to be figurative for the Jewish people of Matthew's own day. New Testament scholars, particularly specialists in Matthew and the Synoptic Gospels will find the volume useful, and it will also appeal to those interested in early Jewish-Christian relations and the "parting of the ways" between the two faiths.